2008
DOI: 10.1007/s12161-007-9011-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial resistance in Vibrio strains isolated from imported seafood and Italian aquaculture settings

Abstract: Ninety-two Vibrio strains isolated over a period of 9 years from different sources (national and imported fishery products, shellfish, seawater from aquaculture settings, etc.) and belonging mostly to two species relevant for human health and fish pathology, V. parahaemolyticus and V. alginolyticus, were tested for resistance to different antibacterials using the standard disk diffusion test (five antibacterials: ampicillin, sulfamethoxazole, tetracycline, trimethoprim/sulfamethoxazole and chloramphenicol) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 41 publications
1
5
0
5
Order By: Relevance
“…Antimicrobial resistance among the V. parahaemolyticus tested revealed that most isolates (87.5%) were resistant to ampicillin (56 of 64 isolates; Table 3). These data are similar to the results from other countries where V. parahaemolyticus of shellfish origin were mainly resistant to p-lactams (ampicillin) (9,10,13,19,31). In other investigations, especially from Asia, 100% of isolates were resistant to this antimicrobial (14,30).…”
Section: Resultssupporting
confidence: 90%
“…Antimicrobial resistance among the V. parahaemolyticus tested revealed that most isolates (87.5%) were resistant to ampicillin (56 of 64 isolates; Table 3). These data are similar to the results from other countries where V. parahaemolyticus of shellfish origin were mainly resistant to p-lactams (ampicillin) (9,10,13,19,31). In other investigations, especially from Asia, 100% of isolates were resistant to this antimicrobial (14,30).…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the transfer of plasmids among bacteria on seafood has been reported [37]. Strains were found to have minimal inhibitory concentrations (MIC) far lower than the MIC requirement for the “resistant” classification, indicating that very low concentrations of antibiotics can select for resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Trimethoprim에 내성을 갖는 장염비브리오는 classs I integron 내에 존재하는 dfrA27 유전자 에 의해 trimethoprim, gentamicin 및 rifampin의 내성에 관여하 는 유전자가 포함되어 있다는 연구결과가 최근에 보고하였다 (Yu et al, 2010 (Lee et al, 2007;Lee et al, 2009). 이러한 결과는 우리나라에만 국한되고 있는 것이 아니라 외국의 예도 유사한 실정이다 (Tanil et al, 2005;Baker-Austin et al, 2008;Ferrini et al, 2008 (Fig. 1A와 B).…”
unclassified